Electronic, Magnetic, and Optical Properties of Metal Adsorbed g-ZnO Systems - Shen, Yang; Yuan, Zhihao; Cui, Zhen; Ma, Deming; Yang, Kunqi; Dong, Yanbo; Wang, Fangping; Du, Ai; Li, Enling (Frontiers in Chemistry, 2022)
2D ZnO is one of the most attractive materials for potential applications in photocatalysis, gas and light detection, ultraviolet light-emitting diodes, resistive memory, and pressure-sensitive devices. The electronic structures, magnetic properties, and optical properties of M (Li, Na, Mg, Ca, or Ga) and TM (Cr, Co, Cu, Ag, or Au) adsorbed g-ZnO were investigated with density functional theory (DFT). It is found that the band structure, charge density difference, electron spin density, work function, and absorption spectrum of g-ZnO can be tuned by adsorbing M or TM atoms. More specifically, the specific charge transfer occurs between g-ZnO and adsorbed atom, indicating the formation of a covalent bond. The work functions of M adsorbed g-ZnO systems are obviously smaller than that of intrinsic g-ZnO, implying great potential in high-efficiency field emission devices. The Li, Na, Mg, Ca, Ga, Ag, or Au adsorbed g-ZnO systems, the Cr adsorbed g-ZnO system, and the Co or Cu adsorbed g-ZnO systems exhibit non-magnetic semiconductor proprieties, magnetic semiconductor proprieties, and magnetic metal proprieties, respectively. In addition, the magnetic moments of Cr, Co, or Cu adsorbed g-ZnO systems are 4 μB, 3 μB, or 1 μB, respectively, which are mainly derived from adsorbed atoms, suggesting potential applications in nano-scale spintronics devices. Compared with the TM absorbed g-ZnO systems, the M adsorbed g-ZnO systems have more obvious absorption peaks for visible light, particularly for Mg or Ca adsorbed g-ZnO systems. Their absorption peaks appear in the near-infrared region, suggesting great potential in solar photocatalysis. Our work contributes to the design and fabrication of high-efficiency field emission devices, nano-scale spintronics devices, and visible-light responsive photocatalytic materials.